Wacana Filosofis Tentang Komponen-Komponen Pendidikan Islam - Fadhilah, Putri; Dani, Rima Rahma (Yayasan Daarul Huda Kruengmane, 2024)
The components of Islamic education in the Qur'an include education in tauhid, education in ibadah, education in ethics or akhlak, education in mental development, and education in life management. The purpose of these components is to develop human potential, including spiritual, emotional, and cognitive-rational intelligence. By understanding and implementing these principles, humans can recognize their true selves and function accordingly, ultimately leading to happiness in both this world and the hereafter.